Structural characterization, molecular modification and hepatoprotective effect of melanin from Lachnum YM226 on acute alcohol-induced liver injury in mice. Issue 8 (3rd August 2016) - Song, Sheng; Li, Shenglan; Su, Nana; Li, Jinglei; Shi, Fang; Ye, Ming
Abstract : In this paper, we obtained the possible structural formula of the intracellular melanin of Lachnum YM226 and evaluated the protective effect of this melanin and itsd -glucosamine-modified product on acute alcohol-induced liver injury in mice. Abstract : In this paper, the possible structural formula of the intracellular homogeneous melanin of Lachnum YM226 (LM) was concluded based on an elemental assay, ultraviolet–visible spectroscopy (UV–Vis), Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), mass spectrometry (MS) and equivalent series resistance (ESR). Meanwhile, ad -glucosamine melanin derivative (GLM) was also prepared and its cytotoxicity was evaluated using the MTT assay. The hepatoprotective effect of LM and GLM was evaluated in an acute alcohol-induced liver injury model. The results showed that pretreatments with LM and GLM markedly decreased subsequent alcohol elicited acute hepatic oxidative and inflammatory stress via improving the activity of antioxidant enzymes (glutathione (GSH), catalase (CAT), glutathione peroxidase (GPX), and total superoxide dismutase (SOD)), reducing hepatic levels of nuclear transcription factor (NF-κB), cytokines related to its activation (interleukin (IL)-6, tumor necrosis factor (TNF)-α and macrophage chemoattractant protein (MCP)-1) and hepatic activities of inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2. The protection properties of alcoholic liver injury of GLM were more obvious than that of LM at the same dose. The present findings recommend that LM and GLM may be used as a prototype for the prevention of alcoholic liver injury.